Where do they come from and where do they go: Understanding the relationship between deprivation and the geographical journeys of trainee doctors in England - Barry Rowlingson; Peter Diggle; Liz Brewster; Michael Lambert (PLoS ONE, 2026)
Having enough doctors to provide healthcare services is a concern internationally. In the UK, significant resources for education and training have been devoted to medical workforce management. Nevertheless, some areas of the country still struggle to recruit and retain staff compared with others. Solutions to this problem have focused on attracting students from backgrounds not traditionally represented in medicine to choose it as a career, and opening new medical schools in different areas of the country. The main objective of this paper is to examine medical student and doctor distribution in order to contribute to understanding the distribution of health and health service inequalities. We used a modelling approach to understand characteristics of medical students, medical schools and foundation schools to interpret and identify the relationship between geographic distribution and socio-economic deprivation. This geographical and statistical analysis aims to identify patterns in workforce distribution, layering these with data on deprivation and inequality. Analysis shows that there are fewer students who come from from more deprived areas, and that different patterns can be observed in geographic locations of training when considering gender and ethnicity. While there is greater diversity of the future workforce in terms of gender and ethnicity, there is evidence that fewer students from more deprived backgrounds are attending medical schools. This has implications for the future workforce, and medical schools may need to play a greater role in increasing access to medical education to overcome observed inequalities.